2015
DOI: 10.3109/0886022x.2015.1074488
|View full text |Cite
|
Sign up to set email alerts
|

Poststreptococcal glomerulonephritis in children with congenital anomalies of the kidney and urinary tract

Abstract: Background: The objective of this study was to assess clinical course and outcome of children with congenital anomalies of the kidney and urinary tract (CAKUT) who had an attack of acute poststreptococcal glomerulonephritis (PSGN). Method: Renal status including blood pressure, proteinuria and glomerular filtration rate was retrospectively analyzed in five children with CAKUT and PSGN at the presentation and during the follow up. Results: In the period 2004-2013, 678 patients were diagnosed and recruited in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…21 Recurrent UTI rarely leads to CKD without any underlying renal abnormalities 22 and has been shown to worsen the prognosis of the patients with congenital kidney diseases and bilateral renal impairment. 23 As noted in previous studies, CKD was significantly observed in patients who had recurrent UTI. However, we did not find UTI as a risk factor for the development of CKD in the current study.…”
Section: Discussionsupporting
confidence: 57%
“…21 Recurrent UTI rarely leads to CKD without any underlying renal abnormalities 22 and has been shown to worsen the prognosis of the patients with congenital kidney diseases and bilateral renal impairment. 23 As noted in previous studies, CKD was significantly observed in patients who had recurrent UTI. However, we did not find UTI as a risk factor for the development of CKD in the current study.…”
Section: Discussionsupporting
confidence: 57%